Erratum: Puscas, I.; et al. IVIVC Assessment of Two Mouse Brain Endothelial Cell Models for Drug Screening. Pharmaceutics 2019, 11, 587 - Ina Puscas; Florian Bernard-Patrzynski; Martin Jutras; Marc-André Lécuyer; Lyne Bourbonnière; Alexandre Prat; Grégoire Leclair; V. Gaëlle Roullin (MDPI AG, 2020)
The authors wish to make the following corrections to this paper [...]